A biomass-based integrated energy system for urea and power production: Thermodynamic analysis - Haya Alyasi (18021976) (2024)
The study aims to optimize the poly-generation of power and urea through the thermochemical conversion of biomass feedstock into hydrogen-rich syngas using steam gasification. This hydrogen-rich syngas serves as a crucial intermediate for producing valuable products, including power and urea. Biomass wastes such as date pits, manure, sludge, and food waste are utilized in this poly-generation process. Using Aspen Plus process modeling software, the system integrates biomass steam gasification with the cogeneration of urea and power, simulating the system's performance. A sensitivity analysis assesses the effects of carbon dioxide utilization and the power-to-urea splitting ratio on the system's overall energy and heat demands. The optimized results of the thermodynamic assessment of the integrated system demonstrate an overall energy efficiency of 52.30% and exergy efficiency of 56.40%, resulting in a power generation of 39.49 MW, a urea production rate of 2.8 kg/s, and a total steam production of 15.56 kg/s. These findings provide valuable insights for determining the optimal power ratio to urea production. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2024.10.113